Interlinkages between the just ecological transition and the digital transformation - Elena Verdolini (European Trade Union Institute (ETUI), 2023)
Notwithstanding increasing policy and academic debate around the 'twin' digital and ecological transitions, there is no systematic assessment of their linkages, potential synergies and trade-offs. Most fundamentally, the full extent of challenges that their interaction poses for the prospects of a 'just transition' is not fully understood. This paper discusses the role and impact of digital technologies on two key objectives of a just sustainability transition, namely (1) the creation of decent-quality employment in (2) the pursuit of climate change mitigation and, more broadly, sustainability. In addition, it also discusses (3) whether and how digitalisation affects society more broadly, with a particular focus on how digital technologies can contribute to or reduce existing inequalities, as well as promote social dialogue at all levels. For each of these three aspects, evidence is presented regarding either the negative or positive effects of a number of digital technologies in several key sectors. Based on this evidence, the rationale for jointly addressing these transformations is explained and key policy implications are put forward.
Keywords: O33; Q52; O15; H23; 330; Just transition; digital transformation; ecological transition